Karen refugee youths' satisfaction with a teen dating violence prevention program. Issue 1 (3rd May 2020) - Ravi, Kristen E.; Black, Beverly M.; Mitschke, Diane B.; Pearson, Katelyn
ABSTRACT: Teen dating violence is a public health problem in the U.S. and internationally. Evaluations of teen dating violence (TDV) prevention programs demonstrate positive changes in youths' knowledge, attitudes, and behavior. Less is known about youths' satisfaction with TDV programming, especially among refugee youth. This study examines the satisfaction of an evidenced-based TDV program among Karen refugee youth ( n = 14) who participated in a pilot study. A 9-item validated satisfaction measure with a 7-point scale was used to rate the youths' satisfaction. The average satisfaction rating was 5.95 ( SD = .49) which indicated that the youth were satisfied with the program without any cultural adaptations; finding it enjoyable and informative. Implications for TDV prevention programs include increasing the number of small-group activities and allocating time to discuss the role of technology in dating violence.